Stem Cell-Derived Exosomes Protect Astrocyte Cultures From in vitro Ischemia and Decrease Injury as Post-stroke Intravenous Therapy - Sun, Xiaoyun; Jung, Ji-Hye; Arvola, Oiva; Santoso, Michelle R.; Giffard, Rona G.; Yang, Phillip C.; Stary, Creed M. (Frontiers in Cellular Neuroscience, 2019)
In the present study we assessed efficacy of exosomes harvested from human and mouse stem cell cultures in protection of mouse primary astrocyte and neuronal cell cultures following in vitro ischemia, and against ischemic stroke in vivo. Cell media was collected from primary mouse neural stem cell (NSC) cultures or from human induced pluripotent stem cell-derived cardiomyocyte (iCM) cultures. Exosomes were extracted and purified by polyethylene glycol complexing and centrifugation, and exosome size and concentration were determined with a NanoSiteTM particle analyzer. Exosomes were applied to primary mouse cortical astrocyte or neuronal cultures prior to, and/or during, combined oxygen-glucose deprivation (OGD) injury. Cell death was assessed via lactate dehydrogenase and propidium iodide staining 24h after injury. Neural stem cell-derived exosomes afforded marked protection to astrocytes following OGD in a dose-dependent manner. A more modest (but significant) level of protection was observed with human iCM-derived exosomes applied to astrocytes, and with NSC-derived exosomes applied to primary neuronal cultures. In subsequent experiments, NSC-derived exosomes were injected intravenously into adult male mice 2h after transient (1h) middle cerebral artery occlusion. Gross motor function was assessed 1d after reperfusion and infarct volume was assessed 4d after reperfusion. Mice treated post-stroke with intravenous NSC-derived exosomes exhibited significantly reduced infarct volumes. Together, these results suggest that exosomes isolated from mouse NSCs provide neuroprotection against experimental stroke possibly via preservation of astrocyte function. Intravenous NSC-derived exosome treatment may therefore provide a novel clinical adjuvant for stroke in the immediate post-injury period.